2017
DOI: 10.1080/21592799.2016.1271498
|View full text |Cite
|
Sign up to set email alerts
|

Rab11-FIP1 phosphorylation by MARK2 regulates polarity in MDCK cells

Abstract: MARK2/Par1b/EMK1, a serine/threonine kinase, is required for correct apical/basolateral membrane polarization in epithelial cells. However, the specific substrates mediating MARK2 action are less well understood. We have now found that MARK2 phosphorylates Rab11-FIP1B/C at serine 234 in a consensus site similar to that previously identified in Rab11-FIP2. In MDCK cells undergoing repolarization after a calcium switch, antibodies specific for pS234-Rab11-FIP1 or pS227-Rab11-FIP2 demonstrate that the spatial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Madin-Darby canine kidney (MDCK) cells represent a well-established cell line model for epithelial morphogenesis research ( Dukes et al., 2011 ; Elia and Lippincott-Schwartz, 2009 ; Datta et al., 2011 ; McRae et al., 2017 ; Sottocornola et al., 2010 ; Pillman et al., 2018 ). Indeed, tens of thousands of papers have been published on using MDCK cells to study epithelial cell polarity, epithelial-mesenchymal transition (EMT) and cancer, tissue engineering, and other subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Madin-Darby canine kidney (MDCK) cells represent a well-established cell line model for epithelial morphogenesis research ( Dukes et al., 2011 ; Elia and Lippincott-Schwartz, 2009 ; Datta et al., 2011 ; McRae et al., 2017 ; Sottocornola et al., 2010 ; Pillman et al., 2018 ). Indeed, tens of thousands of papers have been published on using MDCK cells to study epithelial cell polarity, epithelial-mesenchymal transition (EMT) and cancer, tissue engineering, and other subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the upregulation of RAB11FIP1 and RAB11FIP2 and their interacting partner RAB11a promotes cancer migration and invasion [ 26 29 ]. RAB11FIP1 protects integrins from degradation, regulates cadherin recycling and promotes the expression of EMT-related transcription factors [ 27 , 29 , 31 , 32 , 61 , 62 ]. In this study, we found that circRTN4 promotes EMT via RAB11FIP1-mediated upregulation of N-cadherin, Slug, Snai1, Twist and Zeb1 in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data from a cultured collecting duct cell line, MDCK, provided strong evidence for a central role of another SNF1‐subfamily kinase, viz. Mark2 (Par‐1), in the regulation of collecting duct cell polarity and vesicular trafficking 44‐54 . PKC‐iota is an “atypical” protein kinase C, ie it is calcium‐ and diacylglycerol‐independent, that plays an important role in creating and maintaining epithelial polarity 55 …”
Section: Discussionmentioning
confidence: 99%